Handbook of Green Chemistry 2010
DOI: 10.1002/9783527628698.hgc005
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids and Catalysis: theIFPBiphasic Difasol Process

Abstract: Optimal exploitation of raw materials, energy saving, and environmental friendliness take nowadays a major place in the development of catalytic processes. This implies better use of raw materials, lower formation of side products and, if possible, simplified separation workup steps. In this economical and environmental context, one most successful approach to bridge the gap between homogeneous and heterogeneous catalysis is multiphasic catalysis. In its simplest version, the catalyst is dissolved in one phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 40 publications
0
39
0
1
Order By: Relevance
“…30,31 The new ligands 3 and 7 were prepared by conventional condensation of phenylene diamine with N-alkyl iminodiacetic acid diethylester (see Experimental Section). 3 ] which was characterised by NMR and X-ray diffraction (see Figure 5). …”
Section: Ligand and Complex Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 The new ligands 3 and 7 were prepared by conventional condensation of phenylene diamine with N-alkyl iminodiacetic acid diethylester (see Experimental Section). 3 ] which was characterised by NMR and X-ray diffraction (see Figure 5). …”
Section: Ligand and Complex Synthesismentioning
confidence: 99%
“…[1][2][3][4] Several commercial processes produce LAOs with different distributions of chain lengths.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, 35 licensed DIMERSOL units with typical capacities between 20,000 and 90,000 tons per year are in use for selective dimerization reactions of short chain olefins. [4] About 30 years ago, Wilkes et al and Osteryoung et al reported the first room temperature ionic liquids based on aluminum chloride. [5] In the 1980s, these chloroaluminate ionic liquids were thoroughly investigated in terms of their physical and electrochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the sterics of the bis(trimethylsilylamide) ligand promote mononuclear 3-coordinate structures (9)(10)(11)(12). Mesitylanilido-and triphenylsilyloxo-chlorido species 16 and 18, respectively, dimerize via chlorido bridge formation, while the 3-coordinate DiPPanilido-chlorido derivative 13, that was prepared under carefully controlled conditions in octane, easily conproportionates in polar solvents by ligand redistribution to form the thermodynamically more stable mononuclear 3-coordinate bis(anilido) species 14 and 15.…”
Section: N1 Fe1 Cl1mentioning
confidence: 99%
“…Ethylene, propylene and butenes are in increasing demand [3][4][5][6][7][8][9][10][11][12][13]. Ethylene alone is at the origin of ca.…”
Section: Introductionmentioning
confidence: 99%